Efficiency comparison of ozonation, photolysis, photocatalysis and photoelectrocatalysis methods in real textile wastewater decolorization - Cardoso, Juliano Carvalho [UNESP]; Bessegato, Guilherme Garcia [UNESP]; Boldrin Zanoni, Maria Valnice [UNESP] (Elsevier, 2016)
Treatment of real effluents from industries using AOPs stands to be an imperative task of crucial importance yet quite huge a challenge largely given the nature of complexity of these wastewaters. The present work sought to develop a versatile system aimed at the treatment of real wastewater using a bubbling annular reactor, which enables us to test the efficiency of photolysis; photocatalysis, photoelectrocatalysis and direct ozonation using oxygen or ozone as gas flow. A TiO2 nanotubes electrode was used as photocatalyst in photocatalytic and photoelectrocatalytic measurements with and without coupling with ozonation under pH 3.0 and pH 8.0 leading to 50% of color removal after 60 min reaction. However, the results indicated 90% of color removal upon the bubbling of ozone after 15 min of treatment. A synergistic effect was observed in all experiments using the AOPs in the presence of ozone under both pH values. Interestingly though, 85% of decolorization was obtained through direct ozonation without any change in the effluent following 10 min of treatment. The results were discussed in terms of electric energy per order and were compared to those reported previously. For real textile wastewater, ozonation appears to be a promising candidate for full-scale effluent decolorization.
Keywords: Annular bubble reactor; Decolorization; Ozonation; Photoelectrocatalysis; Textile effluent; TiO2 nanotube arrays